Improving English Language Writing Skills of Sophomore Students of Uzbekistan State World Languages University by Quora Digest (Journal of Pedagogical Inventions and Practices, 2022)
Mastery of writing skills is critical to an academic world and to bring breakthroughs to a field. This action research introduced the application of Quora Digest in English classrooms to analyze its effectiveness in enhancing writing skills of EFL learners. The procedure included using Quora Digest as a platform where students express their opinions in a written form and techniques (such as recognizing vocabulary in context with its context-specific meaning and using it in their expressions) introduced to students to give even better results. The empirical results of the study showed that sophomore students were able to improve their writing level from developing to expanding and fluent levels. In a nutshell, Quora Digest proved effective and successful in promoting students’ writing skills in English classes.